PENGARUH PARTISIPASI ANGGARAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA PT. BANK MANDIRI KCP MMU MEDAN PASAR GAMBIR - Amran Manurung (Visi Sosial Humaniora, 2020)
This research was conducted to measure whether budgetary participation and motivation affect employee performance in banking either partially or simultaneously. The research sample was 33 people, where the sample was selected by saturated sampling method. Based on the results of data analysis and testing described in the previous chapter, some conclusions obtained from this study include: (1) Partially, budget participation has a positive and insignificant effect on the performance of employees of PT. Bank Mandiri KCP MMU Medan Pasar Gambir with a regression coefficient of 0.015 and a data significance of 0.946; (2) Partially, motivation has a positive and insignificant effect on the performance of employees of PT. Bank Mandiri KCP MMU Medan Pasar Gambir with a regression coefficient of 0.320 and a data significance of 0.051. This indicates that employees' high motivation to work will achieve a predetermined standard / goal; (3) Simultaneously, budget participation and motivation together have a significant effect on the performance of employees of PT. Bank Mandiri KCP MMU Medan Pasar Gambir where the value of the Simultaneous Test Coefficient (F) is 35,272 with a data significance of 0,000. This means that participation rates and work motivation can affect employee performance results.